2023
DOI: 10.1097/txd.0000000000001459
|View full text |Cite
|
Sign up to set email alerts
|

An Initial Analysis of the Baseline Levels of Dd-cfDNA After Pancreas Transplantation: A Prospective Study From High-volume Centers in the United States

Abstract: P ancreas transplantation is a nonpharmacologic approach to glucose homeostasis in patients with diabetes associated with better self-identified health scores than insulin alone. [1][2][3] Patients with diabetes are more likely to be alive at 20 y following deceased donor simultaneous pancreas-kidney (SPK) transplant, which is a robust solution for diabetes management. [4][5][6][7][8] Pancreas transplantation is associated with higher rates of rejection-related graft loss than kidney transplantation. [9][10][1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Pancreas and kidney functions were evaluated at each post-operative visit and through regular laboratory screenings. We recorded the number of pancreas and renal transplant biopsies conducted, as well as the clinical reasons for performing them [19].…”
Section: Rejection Classification and Identificationmentioning
confidence: 99%
“…Pancreas and kidney functions were evaluated at each post-operative visit and through regular laboratory screenings. We recorded the number of pancreas and renal transplant biopsies conducted, as well as the clinical reasons for performing them [19].…”
Section: Rejection Classification and Identificationmentioning
confidence: 99%
“…In another study, Williams et al [ 25 ] found that levels of circulating donor cell-free DNA are significantly lower in stable recipients and even those with pancreatitis compared to patients who experienced acute rejection. Researchers in Barcelona explored donor circulating DNA as a diagnostic biomarker before biopsy, finding that assessment of donor-derived DNA 45 days after transplant had the highest specificity and sensitivity to predict acute rejection in biopsy results compared to typical markers like amylase and lipase [ 26 ]. Similarly, multicenter study including SPKT and pancreas transplantation alone (PTA) showed that dd-cfDNA is elevated within 3 months after transplant, regardless of the type of transplantation and presence of infection or rejection [ 27 ].…”
Section: Pancreas Transplantationmentioning
confidence: 99%